Double J/ψ production in pion-nucleon scattering at COMPASS; Physics Letters B; Vol. 838 - Alekseev G. D. Gennady Dmitrievich; Alekseev M. G. Maksim Gennadjevich; Amoroso A.; Burtsev V. E. Vitaly Evgenjevich; Chumakov A. G. Aleksandr Grigorjevich; Dusaev R. R. Renat Ramilyevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Mamon S. A. Sergey Aleksandrovich; Sharko K. A. Konstantin Andreevich (2023, 2023)
Title screen